PERAN GURU DALAM PELAKSANAAN BIMBINGAN BELAJAR DI UPTD SD NEGERI KENARILANG - Anastasia Laubela; Anamalinda Fanmaley, Acia Blegur La, Yessy Mata, Petrus Mau Tellu Dony, Yermia S. Wabang (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to find out the role of teachers in the implementation of tutoring at UPTD SD Negeri Kenarilang. The method used is qualitative description with data collection techniques through observation, interviews and literature review. The results of the study show that the role of teachers is very important in overcoming in helping students overcome learning difficulties through tutoring that is carried out outside school hours. Teachers play the role of facilitators, motivators, and companions in identifying internal and external factors that cause learning difficulties, as well as providing solutions through remedial activities. The implementation of tutoring has been proven to improve learning outcomes and student motivation even though faced with the challenge of limited time and student activities outside of school.